Western Lampung Offshore Wind and Wave Data Correlation Analysis - Hermanto, Mochammad Fathurridho; Nandalianadhira, Nafisa; Puspita, Eka Suci; Hutajulu, Iin Debora (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2024)
Wind and waves are the two most dominant environmental parameters in the sea. The availability of these two data is crucial in the design process of offshore and onshore buildings and the development of renewable energy from wind or wave. Numerous analyses have been done on each parameter, but none have tested their correlation specifically in the waters of the western Lampung. This study aims to find a correlation between these two parameters. The study used 20 years of wind and wave data from BMKG. The average wind speed data obtained was about 4,17 - 5,13 m/s. The mean significant wave height obtained was about 1,89 - 2,09 m. BMKG gives more direction with a huge wind-blowing duration (more than 500 hours), wind-blowing direction data are dominantly from SSE, WNW, and WSW. However, wave direction data is going to N and NE. This study found no correlation between wind and wave direction on the Western Lampung Offshore. Based on data from the time series of wind and wave that have been analyzed, continuously higher wind speeds result in higher wave heights.